Epidemiology and treatment patterns of UK women diagnosed with vasomotor symptoms: Findings from the Clinical Practice Research Datalink GOLD database. (October 2022) - Kiran, Amit; Schultz, Neil M.; Siddiqui, Emad; Todorova, Lora; Van der Poel, Bas; Stoelzel, Matthias; Robinson, Lynne
Highlights: This study found the incidence of vasomotor symptoms to be stable over the period 2009–2018 for women aged 40–65 years. A third and a half of women diagnosed with vasomotor symptoms were initiated on non-hormonal and hormonal treatments, respectively. Variations in the patterns of prescribed treatment suggest that education may be needed for clinicians and women. Women persisted with their initial treatments for a median of 4 months. Abstract: Objectives: To describe the epidemiology and treatment of vasomotor symptoms (VMS) in the UK. Study design: Retrospective study that used electronic medical records from UK primary care centers. Main outcome measures: The prevalence and incidence of moderate-to-severe VMS, the proportion treated, persistence with initial treatment, treatment patterns, and menopausal hormone therapy (HT) experience were investigated over the study period (Jan. 2009–Dec. 2018). The study population comprised women aged 40–65 years registered at general practitioner clinics. For incident cases, the uptake of pharmacological non-hormonal or hormonal treatment was recorded, which included experience of HT. Results: Over the 10-year study period, 1, 481, 646 women were included from the database, among whom there were 313, 031 prevalent and 90, 434 incident cases of VMS. Annual prevalence and incidence rates were stable over time, with a weighted average of 21.1 % and 15.3 per 1000 person-years, respectively (results varied across age groups). Among women who were incident VMS cases, 32.4 % (29, 275) were initially prescribed non-hormonal treatments for a median of 3.9 months, 49.4 % (44, 700) were prescribed hormonal treatments for 4.0 months, and 18.2 % (16, 459) had no treatment. Approximately one-third of treated women switched between non-hormonal and hormonal treatments. The HT experience results showed that 52.7 % (47, 639) of women were HT-eligible, 13.1 % (11, 872) were HT-contraindicated (they may or may not have received HT), and 34.2 % (30, 923) did not receive HT. Conclusions: Variations in prescribed treatment patterns suggest that education may be needed for clinicians and women regarding the potential pharmacological options for treating VMS in the UK.